2001
DOI: 10.1142/s0129183101001626
|View full text |Cite
|
Sign up to set email alerts
|

An Adapted Symplectic Integrator for Hamiltonian Problems

Abstract: In this paper, a new procedure for deriving efficient symplectic integrators for Hamiltonian problems is introduced. This procedure is based on the combination of the trigonometric fitting technique and symplecticness conditions. Based on this procedure, a simple modified Runge–Kutta–Nyström second algebraic order trigonometrically fitted method is developed. We present explicity the symplecticity conditions for the new modified Runge–Kutta–Nyström method. Numerical results indicate that the new method is much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 5 publications
0
14
0
3
Order By: Relevance
“…The floristic and syntaxonomic characterisation of plant communities has been performed according to the concepts and methods of classical phytosociology, thoroughly revised in the literature for the last two decades (Gehu & Rivas-Martinez, 1981;Alcaraz, 1996;Aguiar & Honrado, 2001;Rivas-Martinez, 2002;Honrado, 2003). In short, phytosociolo- gical releves were performed in representative formations with widely repeatable (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The floristic and syntaxonomic characterisation of plant communities has been performed according to the concepts and methods of classical phytosociology, thoroughly revised in the literature for the last two decades (Gehu & Rivas-Martinez, 1981;Alcaraz, 1996;Aguiar & Honrado, 2001;Rivas-Martinez, 2002;Honrado, 2003). In short, phytosociolo- gical releves were performed in representative formations with widely repeatable (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Surveys of the literature with numerous references and useful bibliography and a review of these methods can be found in detail in [1,2,25,27,32,34]. These nonlinear equations can be also solved using an exponential fitting method proposed by Vigo-Aguiar et al [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…, c q the Gauss nodes in the interval [0, 1] we have the super convergent methods with maximum order p = 2q which are both symplectic and symmetric (see [5], p. 28 and p. 179). Methods that are exact for other spaces of functions F such as trigonometrical polynomials, exponential functions or mixed algebraic and trigonometrical polynomials suitable for special types of differential equations have been considered in [1,3,4,6,7,10,11,[13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%